Historia mínima de Uruguay - Caetano, Gerardo (Historia mínima (Mexico City, Mexico), 2020)
Informed and well written history of Uruguay. Weaves together threads of nearly five centuries of nation's past in synthetic narration of carefully selected processes, events and agents. Author is Uruguayan former professional soccer player and esteemed historian and political scientist.